PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS X SMK MUHAMMADIYAH 2 PEKANBARU - Nurjannah, Ike; Saragih, Sehatta; ', Syofni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: The background of this study is students low in mathematical of  X grade at SMK Muhammadiyah 2 Pekanbaru and never doing to implementation problem based learning model. This research conducted in second semester of academic years 2016/2017. The aimed of study is to find out whether there is significant effect of using “problem based learning model” toward students mathematical of X grade at SMK Muhammadiyah 2 Pekanbaru. The study employed the pre-experimental research focus on static group comparison study design. The sampling of technique was purposive. There were two sampling in this study; the experimental class was using “problem based learning model” and the control class with conventional learning. In collecting data used daily test as pre-test and test scores as post-test whether to see how the students ability in before and after giving a treatment. The finding of this research showed experimental class better than control class. So, it can be concluded  there was significant effect of using problem based learning model toward student’s mathematical of X grade at SMK Muhammadiyah 2 Pekanbaru.